2006
DOI: 10.1007/s00213-006-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

Valproate blocks high-dose methamphetamine-induced behavioral cross-sensitization to locomotion-inducing effect of dizocilpine (MK-801), but not methamphetamine

Abstract: These results suggest that VPA inhibits high-dose METH-induced delayed increases in Glu levels to prevent development of behavioral cross-sensitization to an NMDA antagonist, but not sensitization to METH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…[2] and NAC [13,14], which might play an important role in the development of repeated METH-induced PPI disruption and behavioral cross sensitization to an NMDA receptor antagonist, MK-801. In this study, LTG (30 mg/kg) administered 120 min after METH (2.5 mg/kg) injection blocked the METH-induced glutamate increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] and NAC [13,14], which might play an important role in the development of repeated METH-induced PPI disruption and behavioral cross sensitization to an NMDA receptor antagonist, MK-801. In this study, LTG (30 mg/kg) administered 120 min after METH (2.5 mg/kg) injection blocked the METH-induced glutamate increase.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has demonstrated that a single administration of METH, at 2.5 mg/kg, increases the extracellular glutamate levels in the mPFC [2] and the nucleus accumbens (NAC) [13,14]. Furthermore, repeated administration of METH (2.5 mg/kg) induces apoptosis in the mPFC.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that 2.5 mg/kg, but not 1.0 mg/kg of METH induced increases in glutamate levels in the mPFC [1] and the nucleus accumbens [14,15], suggesting that repeatedly increased glutamate release in the neuronal circuit, which comprises the mPFC and nucleus accumbens, is related to the METH-induced long-lasting PPI deficit. Furthermore our group [1] found that several drugs such as olanzapine and risperidone, which block METH-induced delayed increase in extracellular glutamate levels in mPFC, prevented the initiation of PPI deficit induced by the repeated administration of METH.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, expression of the neuroplastic PPI deficit induced by the repeated administration of METH might reflect the state underlying hypofunction of NMDA receptors [15]. The PPI deficit is induced acutely by hypofunction of NMDA receptor-mediated glutamatergic neurotransmission by a single administration of NMDA receptor antagonists [4].…”
Section: Discussionmentioning
confidence: 99%
“…That dosage, but not 1.0 mg/kg (which increases extracellular dopamine levels but not glutamate levels), can increase both extracellular glutamate and dopamine levels in the medial prefrontal cortex (mPFC) [1,2]. It induces schizophrenia-related behavioral and histological abnormalities including cross-sensitization to the NMDA receptor antagonist, a neuroplastic prepulse inhibition (PPI) deficit, and an apoptotic reaction in the mPFC [1,2,10,11,15,16].…”
Section: Introductionmentioning
confidence: 99%